CLINICO-PATHOLOGICAL FEATURES OF GRANULAR CELL ASTROCYTOMA - Hussain, Shabbir; Qamar uz Zaman, Amna; Siddiqui, Tariq; Perry, Arie (Journal of Ayub Medical College Abbottabad, 2021)
We report a rare case of Granular cell astrocytoma (GCA) in a 59 years old male and the dilemma related to its histopathological diagnosis. As Granular cell Astrocytoma cells resemble macrophages this case is important in the pitfalls in its diagnosis and this report emphasizes on the issues related to it. This particular patient had neurological complaints for 7 months and was not investigated. Later he had a CT scan followed by a contrast-enhanced MRI of the Brain that showed multiple focal lesions with surrounding oedema. After metastatic workup with PET/CT scan which was negative; he underwent craniotomy and biopsy of the lesion, which at first was reported as benign. Later his blocks were sent abroad and on further immunohistochemical markers it was finally reported as Granular Cell Astrocytoma (Granular cell Astrocytoma). Granular cell Astrocytoma is a very rare subtype of glioblastoma, which was first described by Markesbery et al in 1973 as a granular cell tumour (GCT) in the brain/central nervous system. GCAs are rare and highly aggressive brain tumours. The cells of GCA are distinguished from macrophages by their expression of glial immune-stains, including glial fibrillary acidic protein (GFAP). The perplexity in diagnosing GCA in this case and its similar characteristics as other benign conditions; makes it a unique rare brain tumour on which we should keep an eye on when we have a fix in diagnosis of similar brain lesions.